AUTHOR’S SOCIAL IMPACT IN AMANDA GORMAN’S SELECTED POEMS - A.Irwin Irham; Dahlan, Sandra Dewi; Taufik, Muhammad (Elite : English and Literature Journal, 2024)
Social impact in this research refers to the influence of Amanda Gorman's literary works on society, especially in fighting for values such as equality, courage and solidarity. Gorman's work not only reflects her personal experiences but also has the power to inspire social change and strengthen human connections at various levels of society. This study examines how Amanda Gorman's life experiences and perspectives are expressed through her selected poems. The data were taken from the Encyclopedia Britannica, Amanda Gorman's own website, an exclusive interview with The Associated Press, Amanda Gorman's poems entitled "The Hill We Climb" (2021), "An Ode We Owe" (2022), and "Chorus of the Captains" (2021). This research is a qualitative descriptive approach and applies Sociology of Literature theory as outlined by renowned scholars Wellek and Warren. The novelty in this research lies in the analysis of Amanda Gorman's poetry by expanding the focus from three main concepts (Social Background, Ideology, and Social Integrity) to seven more detailed concepts. The results of this research reveal that Amanda Gorman's poetry reflects seven main concepts: Personal Struggles and Triumphs, Urban Experience, Cultural Identity and Heritage, Activism through Art, Intersectionality of Gender and Race, Community Building, and Moral and Ethical Advocacy. Gorman draws on her personal experiences and cultural identity to convey social issues through poetry, which reinforces messages of solidarity, justice, and change in society.